(untitled) - Bentham, Sunsan (London, 2005)
Challenging behavior amongst pupils is as much of a headache for teaching assistants as it is for teachers. This book, specifically written with teaching assistants in mind, looks at common behavior problems in the classroom, explains typical causes of misbehavior and shows what teaching assistants can do to tackle and tame disruptive students in their care.
Keywords: Classroom management,School children; United states,United states